Analysis of essential mathematics concepts for fluently to study of chemistry - Fahyuddin Fahyuddin (SAINS : Jurnal Kimia & Pendidikan Kimia, 2012)
This study aimed to identification and analysis of basic mathematical concepts that are widely used in studing chemistry, and so as a main required for the good understanding of quantitative chemistry. Chemistry concepts that can be represented in mathematical models, graphs, and tables of numerics were explored from several chemistry textbooks, that it is as the reference classes in college in the first and second years. The structures and properties of mathematical concepts that its have the same with to mathematical models that became the representation of chemistry concepts defined as the mathematical concepts needed to study chemistry. The results of the analysis of structural similarity between mathematics and chemistry concepts suggested that a number of essential mathematics concepts that support the understanding of chemistry, including: numbers, arithmetic operations (arithmetic), approximation, ratios, proportions, scientific notation, computation notation, logarithmic, exponential, laws of algebra, functions, graphs, system of equations, differential, and integral. The concept of algebra is the most widely used in learning or problem solving in quantitative chemistry. Chemistry students who have lack of undesrstanding of such theses mathematics concept will have difficulty to solving quantitative chemistry problems or studing chemistry. So that, those of essential mathematics concepts should became literacy of mathematics for students of chemistry. Each of concept of essential mathematics can be used in studying several quantitative chemical concepts. Conversely, some quantitative chemical concepts, such as a buffer solution, kinetics, and thermodynamics requires an understanding of a number of essential mathematical concepts.